2018
DOI: 10.1071/ch18197
|View full text |Cite
|
Sign up to set email alerts
|

Gold- and Silver-Catalysed Cyclisation Reactions of β-Amino Allenes

Abstract: Herein we report the formation of pyrrolines and tetrahydropyridines from the cyclisation reactions of β-amino allenes by both AuI and AgI catalysts in yields ranging from 5 to 70 %. AuI catalysts favour a 5-endo-dig cyclisation before rapid rearrangement to the 5-exo-dig product, while AgI favours a 6-endo-trig cyclisation. We also report the first known Ag2O catalysed cyclisation reaction of an allene which occurred in good yield (61 %).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Pyne et al reported the cyclization of b-amino allenes 219 by gold and silver catalysis to afford the pirrolines 220a via a 5endo-dig cyclization to 220b and subsequent isomerization to the more stable isomer 220a (Scheme 70). 124 Under gold catalysis, the optimal conditions consist of using 10 mol% of (PPh 3 ) AuCl/AgBF 4 in acetonitrile at room temperature. b-amino allenes 219 provided the pyrroline 220a and the pyrrolidine 220b with 70% isolated yield in a ratio (220a/220b ¼ 1.…”
Section: Synthesis Of 2-pyrrolinesmentioning
confidence: 99%
“…Pyne et al reported the cyclization of b-amino allenes 219 by gold and silver catalysis to afford the pirrolines 220a via a 5endo-dig cyclization to 220b and subsequent isomerization to the more stable isomer 220a (Scheme 70). 124 Under gold catalysis, the optimal conditions consist of using 10 mol% of (PPh 3 ) AuCl/AgBF 4 in acetonitrile at room temperature. b-amino allenes 219 provided the pyrroline 220a and the pyrrolidine 220b with 70% isolated yield in a ratio (220a/220b ¼ 1.…”
Section: Synthesis Of 2-pyrrolinesmentioning
confidence: 99%
“…Subjecting N -Boc β-allenylamine 2a to cyclization conditions, previously described by our group for β-allenols, did yield a 5:1 ( anti : syn ) mixture of anti - 16 and syn - 16 . A slightly modified literature procedure allowed cyclization of the N -Ts allenylamine 11 into tetrahydropyridin 17 in 71% yield (58% from N -Boc amine 2a ). The allene function in 2a can be directly addressed by rhodium catalyzed addition of benzoic acid to the allene .…”
mentioning
confidence: 99%